PESANTREN DAN PERUBAHAN SOSIAL - Ismail, Muchammad (The Sociology of Islam, 2011)
The growth of Pesantren as a traditional Islamic boarding school in the urban area has demonstrated that there have been changes in the pesantren itself. Some examples of Pesantren existing till now in urban areas are Pesantren for students Al-Hikam Malang, Pesantren for Students An-Nur Surabaya, and Pesantren Luhur Al-Husna Surabaya. Those three pesantren, at least there are two changes emerging in Pesantren tradition. First, from educational system perspective, not only teaching classical Islamic intellectualism, Pesantren have been also teaching modern sciences to their students which called Santri. Second, from leadership perspective which Pesantren have their unique leader called Kyai, Pesantren recently produce the concept of â€˜Kyai Nasibâ€™ as a specific typology for Islamic leaders who are chosen not because of their relation with the former Kyai nor descendants of Kyai, but because of their piousness, spirituality, managerial knowledge and charisma. Kata Kunci: pesantren, perubahan sosial, Kyai, â€œKyai Nasibâ€, kharisma